CLOUD COMPUTING ADOPTION:A CASE STUDY AT BANK TEPAT SYARIAH - Wirya Putra, Tirta
Cloud computing involves using a network of internet-based servers to maintain, store, manage, process, analyze, and protect data. This means data is stored in the cloud rather than on physical devices. By doing so, organizations can improve administration, streamline operations, boost productivity, reduce costs, and enhance the digital customer experience. Despite experiencing rapid data growth, Indonesia and its banking sector have not fully embraced cloud computing due to regulatory challenges and insufficient infrastructure. The primary reason banks hesitate to adopt innovative technologies is the significant cost of developing customized banking solutions, alongside the necessary investment of time and high-quality resources. Cloud computing, the latest technology presents both benefits and challenges. To mitigate the uncertainty and apprehension among decision-makers, it is essential to study the factors influencing cloud computing adoption before implementation. This research aims to identify the technological, organizational, and environmental factors affecting Bank Tepat Syariah's decision to adopt cloud computing, thereby aiding decision-makers in making well-informed choices. The study’s findings indicate that there are ten key factors influencing the decision to adopt cloud computing within Bank Tepat Syariah, namely: Compatibility, Scalability, Complexity, Cost Efficiency, Communication Process, Organization Size, Talent Readiness, Competitive Advantage, Standardization, Regulations. Except for Scalability, Cost Efficiency, and Competitive Advantage, most factors were found to hinder and delay the adoption of cloud computing within Bank Tepat Syariah. These key factors are interconnected in various ways, with one factor influencing another in the decisionmaking process regarding cloud computing adoption